CoboDeck: A Large-Scale Haptic VR System Using a Collaborative Mobile Robot - Mortezapoor, Soroosh; Vasylevska, Khrystyna; Vonach, Emanuel; Kaufmann, Hannes (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2023)
We present CoboDeck - our proof-of-concept immersive virtual reality haptic system with free walking support. It provides prop-based encountered-type haptic feedback with a mobile robotic platform. Intended for use as a design tool for architects, it enables the user to directly and intuitively interact with virtual objects like walls, doors, or furniture. A collaborative robotic arm mounted on an omnidirectional mobile platform can present a physical prop that matches the position and orientation of a virtual counterpart anywhere in large virtual and real environments. We describe the concept, hardware, and software architecture of our system. Furthermore, we present the first behavioral algorithm tailored for the unique challenges of safe human-robot haptic interaction in VR, explicitly targeting availability and safety while the user is unaware of the robot and can change trajectory at any time. We explain our high-level state machine that controls the robot to follow a user closely and rapidly escape from him as required by the situation. We present our technical evaluation. The results suggest that our chasing approach saves time, decreases the travel distance and thus battery usage, compared to more traditional approaches for mobile platforms assuming a fixed parking position between interactions. We also show that the robot can escape from the user and prevent a possible collision within a mean time of 1.62 s. Finally, we confirm the validity of our approach in a practical validation and discuss the potential of the proposed system.